Sapiential insights for ultimate wisdom and intelligence appraising the Qur'an and science - Alvi, Ayesha; Rizwan, Mohammed (Journal of Islam and Science, 2023)
The human body is an extremely intricate work of art, with systems and organs interacting to create what has been acknowledged as life. Among these intricate relationships, one of the most fascinating and significant is the one that has been recently discovered between the gut, the brain, and the heart. This discovery has potentially changed our fundamental reductionist, positivist and more precisely biochemical understanding of higher consciousness, wisdom intelligence etc, paving way for a more holistic comprehension which includes philosophical and epistemological analysis. More importantly, such changed paradigm, challenges the accepted dualisms and invites serious research to explore the interconnectedness of mind, body, and emotion. However, these discoveries sparked a surge of discussions among diverse Muslim scholars and researchers who seek to understand the Qur'anic concept of heart-interceded wisdom, as well as the reasons why the Qur'an insist and talks about heart as a reflection of man’s religiousness or piety. It is important to keep in mind that science and the Qur'an are two different discipline each with their own set of argument and approaches. For instance, science is an always changing discipline due to technological innovations while, the teachings of the Qur'an are constant, ageless, occasionally metaphorical or allegorical. In the light of this intricate landscape, science and the Qur'an may either support or challenge each other on various matters. Therefore, it is imperative to note that scientific knowledge should not be regarded as the ultimate source for comprehending the Qur'an. Nonetheless, many individuals explore scientific findings to deepen their faith and their comprehension of the Qur'an. So, in this exploratory article, we will delve into the heart-gut-brain relationship, its scientific underpinnings, and the implications it holds for our understanding of Qur'anic teachings, health, emotions, and consciousness.